A crucial role for the cortico‐striato‐cortical loop in the pathogenesis of stroke‐related neurogenic stuttering. Issue 9 (25th March 2012) - Theys, Catherine; De, Luc; Thijs, Vincent; van, Astrid; Sunaert, Stefan
<x xml:space="preserve">Abstract</x> Neurogenic stuttering is an acquired speech disorder characterized by the occurrence of stuttering‐like dysfluencies following brain damage. Because the onset of stuttering in these patients is associated with brain lesions, this condition provides a unique opportunity to study the neural processes underlying speech dysfluencies. Lesion localizations of 20 stroke subjects with neurogenic stuttering and 17 control subjects were compared using voxel‐based lesion symptom mapping. The results showed nine left‐hemisphere areas associated with the presence of neurogenic stuttering. These areas were largely overlapping with the cortico‐basal ganglia‐cortical network comprising the inferior frontal cortex, superior temporal cortex, intraparietal cortex, basal ganglia, and their white matter interconnections through the superior longitudinal fasciculus and internal capsule. These results indicated that stroke‐induced neurogenic stuttering is not associated with neural dysfunction in one specific brain area but can occur following one or more lesion throughout the cortico‐basal ganglia‐cortical network. It is suggested that the onset of neurogenic stuttering in stroke subjects results from a disintegration of neural functions necessary for fluent speech. Hum Brain Mapp 34:2103–2112, 2013. © 2012 Wiley Periodicals, Inc.